Mentoring and art: a bio-critical engagement of Ulli Beier and Duro Ladipo's lives (2018)
Several studies on Ulli Beier and Duro Ladipo have established that they were precursors in the development and preservation of aspects of Nigerian indigenous theatrical arts. There have been polemics arising from the critical opinions about the relationship that existed between these two artists and the implication of the influences they wielded, one on the other. Diverse forms of mentoring, an established system of a co-creative process, is identified as the informal but effective ideology that sustained and reinforced the Beier-Ladipo collaboration. This study bio-critically explores two biographical works, Wole Ogundele's Omoluabi: UlliBeier, Yoruba Society and Culture and Aderemi Raji-Oyelade, Sola Olorunyomi and Abiodun Duro-Ladipo's Duro Ladipo: Thunder God on Stage. The paper engages their subjects beyond their lives to their creative passions that impacted Nigeria as well as the international communities beyond their lifetimes. The unmistakable significance of mentorship as agency in the Beier-Ladipo collaboration culminated in the emergence of two dramatists, the Duro Ladipo School and a historical form of the Nigerian operatic travelling theatrical tradition. Examining these antecedents is with a view to interrogating the contemporary value on mentoring relationships on the preservation of culture in spite of diversity.